Internal financial control and financial management in the public sector and their role in the defense system - Kostić Radan O.; Žugić Rade; Radojković Milica (Војно дело, 2014)
The basic concept of control is to create a process that ensures the achievement of objectives with appropriate quality, funds preservation and management in compliance with law and other regulations and procedures, and the preparation and development of reliable financial and business reports. The business compliance is a requirement for the business to be in conformity with the applicable laws, regulations, standards, agreed policies, postulates, and all the patterns of behavior that make the processes legal and socially acceptable. Implementation of internal financial control in the defense system provides and enables efficient and rational use of funds for financing the defense expenditures, on the one hand, and on the other hand, significantly reduces the possibility of irregularities, fraud, corruption, and occurrences of organized crime.